2021
DOI: 10.7759/cureus.19179
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Outcomes of the Implementation of Case-Based Anatomy Learning

Abstract: Purpose: Clinically-oriented anatomy education has been proposed as an effective strategy in anatomy curricula. We aimed to explore the level of extent the literature supports the fact that case-based learning (CBL) can play a significant role in anatomy education. Materials and methods: We searched PubMed, Scopus, Education Resources Information Center (ERIC), and Cochrane database to find articles with the purpose to explore the educational outcomes of case-based anatomy learning. We extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It can not only arise students' interest in learning, but also help them understand the anatomical structures. As is revealed in some studies, the use of CBL in anatomy courses has shown favorable results in terms of students' examination scores, self-con dence, enjoyment, motivation, and ability to facilitate their anatomical learning [10] .…”
Section: Discussionmentioning
confidence: 92%
“…It can not only arise students' interest in learning, but also help them understand the anatomical structures. As is revealed in some studies, the use of CBL in anatomy courses has shown favorable results in terms of students' examination scores, self-con dence, enjoyment, motivation, and ability to facilitate their anatomical learning [10] .…”
Section: Discussionmentioning
confidence: 92%
“…By using typical cases as learning materials and requiring extensive literature reviews, TCLEBL cultivates students’ clinical thinking and problem-solving skills, and improves their evidence-based learning methods and clinical/research abilities. This is a combination of the advantages of CBL [ 24 , 25 ] and EBL [ 26 ]. Lastly, TCLEBL combines traditional teacher-led instruction, in which teachers provide guidance to help students grasp key knowledge points, and research methods, consolidating learning outcomes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case-based learning (CBL) is an innovative method introduced to facilitate a good understanding of the anatomical bases of disease [ 49 ]. It is used in medical education to make anatomy, which can be dull and dry, interesting and clinically relevant [ 50 ]. Students report that CBL helps with the clinical application of anatomical concepts, problem-solving skills, and peer interactions and is an effective approach to initiating student-centered learning [ 49 ].…”
Section: Case-based/problem-based Learning In Anatomymentioning
confidence: 99%